RESCUE BOATS - Dittmer, Lori (Mankato, Minnesota : Creative Education and Creative Paperbacks, 2019)
A basic exploration of the parts, equipment, and variations of rescue boats, the nautical rescue vehicles. Also included is a pictorial diagram of the important rescue vehicle and its equipment.
Rescue Boat Beginnings Types of Hulls Small and Large Constant Communication Rescue Crew Rescue Boats at Work Amazing Rescue Boats Rescue Boat Blueprint.
Includes bibliographical references and index.
Keywords: Search and rescue boats -- Juvenile literature; Emergency vehicles -- Juvenile literature; Rescue work -- Juvenile literature